Інформаційна складова механізму управління сталим розвитком соціально-економічної системи України - Бандура, М.В. (Економіка промисловості, 2013)
Розглянуто сучасні проблеми розробки інформаційної складової механізму управління сталим розвитком соціально-економічної системи та промисловості України, а також визначено основні етапи її реалізації; обґрунтовано необхідність подальшої інформатизації українського суспільства на основі концепції електронного уряду.
Ключові слова: механізм управління сталим розвитком, соціально-економічна система, економіка промисловості, інформаційна складова механізму, інформатизація суспільства. Рассмотрены современные проблемы разработки информационной составляющей механизма управления стабильным развитием социально-экономической системы и промышленности Украины, а также определены основные этапы ее реализации; обоснована необходимость дальнейшей информатизации украинского общества на основе концепции электронного правительства.
Ключевые слова: механизм управления стабильным развитием, социально-экономическая система, экономика промышленности, информационная составляющая механизма, информатизация общества. The stirring up ofresearch and the intensificationof technological innovationstomass useare accompanied bythe formation ofan extremelylarge-scale andhigh-valueinformation flowsthat cansignificantlyaffect the development ofthe world'ssocio-economic systems. This causes theurgencyof buildinga safesystem of accumulationand storageof information, andprovides a high levelof research intensityanditseconomic value.
In this article the contemporary issuesof development of informationcomponent ofthe control mechanism of stable development of socio-economic system of Ukraine and the mainstages of itsimplementation have been considered. The information supportmechanismof socio-economic development of the countrycan be regardedas a collectionof individual structuralelements – thesub-form, process, information sharing and decision-making. Eachsubsystemincludes a number ofspecific tasks, thereby providing the means for achieving congruence between differentlevels of governmentin the processof making importantdecisions insocio-economic sphere.
It has been justified the necessity of further informatization of Ukrainian society based on the concept of e-government. Ukraine has the potential to develop sustainable information infrastructure, but the implementation of such a strategy is complicated by the number of unresolved social and political issues that exist in the state and hamper the process of economic reform.
The gradual informatization of Ukrainian society provides the deepening of relationship and integration of management functions of individual government agencies, promotes the formation of a common information base, aims to provide broadband access to the necessary data, thus accelerating resolving problems not only in the field of management functions, but also during a dialogue with the population. A clear division of responsibilities, the implementation of systematic monitoring and consolidation of financial responsibility can improve the efficiency of the implementation of decisions taken in practice, and therefore the construction of such models is a vital need for the Ukrainian society today.
Keywords: control mechanism of stable development, socio-economic system, industrial economics, information component of mechanism, informatization of society.